2011
DOI: 10.1016/j.pscychresns.2011.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum volume in high-risk offspring from multiplex alcohol dependence families: Association with allelic variation in GABRA2 and BDNF

Abstract: Offspring from families with multiple cases of alcohol dependence have a greater likelihood of developing alcohol dependence (AD) and related substance use disorders. Greater susceptibility for developing these disorders may be related to structural differences in brain circuits that influence the salience of rewards or modify the efficiency of information processing and AD susceptibility. We examined the cerebellum of 71 adolescent/young adult high-risk (HR) offspring from families with multiple cases of alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 78 publications
2
62
2
Order By: Relevance
“…Maternal alcohol dependence during pregnancy was not present. Also, maternal use of alcohol has proved to be of minimal significance in statistical analysis of cerebellar data acquired from this sample [75]. …”
Section: Discussionmentioning
confidence: 99%
“…Maternal alcohol dependence during pregnancy was not present. Also, maternal use of alcohol has proved to be of minimal significance in statistical analysis of cerebellar data acquired from this sample [75]. …”
Section: Discussionmentioning
confidence: 99%
“…Some of the previously published studies examined differences in brain volume between groups in a dichotomous fashion, such as comparing youth with and without familial alcoholism (Hanson et al, 2010), whereas others took a similar approach but included ultra-high-risk youth with multiplex familial AUDs in the family history group, thereby comparing high-and low-risk groups with very distinct levels of vulnerability toward AUDs (Hill et al, 2001(Hill et al, , 2007(Hill et al, , 2009(Hill et al, , 2011(Hill et al, , 2013a(Hill et al, , 2013b. However, the current study examined the degree of familial risk for alcoholism and its relationship with brain volume in a large cohort of youth all considered at risk because of the presence of at least one second-degree relative with an AUD.…”
Section: Discussionmentioning
confidence: 99%
“…Research using a region of interest (ROI) approach has found greater cerebellar volume (Hill et al, 2007(Hill et al, , 2011 and consistently smaller amygdalar and hippocampal (Benegal et al, 2007;Hanson et al, 2010;Hill et al, 2001Hill et al, , 2013b volumes in youth and young adults with familial alcoholism compared with controls. This suggests that morphometric characteristics of the brain may be particularly important markers of risk, but that structural variation related to risk may be present across brain areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the continuous ethyl alcohol ingestion at high doses has risk effects on the cerebellum and its neurons especially Purkinje cells (Fitzgerald et al, 2011;Hill et al, 2011;Heaton et al, 2012). The principal aim of this study was *Corresponding author.…”
Section: Introductionmentioning
confidence: 99%